Muscle pain: diagnosis and treatment - Mense, Siegfried; Gerwin, Robert D. (SpringerLink Bücher, 2010)
The companion volume to Muscle Pain: Understanding the Mechanisms, this text shifts the emphasis from concepts to practical advice. It facilitates the diagnosis and management of the often enigmatic symptoms of chronic muscle pain